Prospects For the Use of Cryptocurrency Payments in The Retail Automotive Services Industry - Artur Tatevosian (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
The article presents a broad analysis of the prospects for using cryptocurrency payments in the retail automotive services industry. The study is conducted within an interdisciplinary paradigm that combines elements of digital economy, blockchain technologies, institutional regulation, and applied models of consumer behavior. Special attention is given to comparing empirical data on trust, intention, and user recommendations with the technical characteristics of consensus algorithms and peer-to-peer payment systems. Based on the analysis of recent studies, barriers and drivers of cryptocurrency adoption are examined, including issues of authentication security, network scalability, and resilience to fork risks. It is revealed that trust acts as the decisive factor for the acceptance of digital currencies, while technological reliability forms the foundation for institutional legitimacy and the scaling of payment practices. The study emphasizes the necessity of a comprehensive approach in which social attitudes and regulatory support strengthen the perception of reliability, while optimized blockchain mechanisms ensure transparency and transaction speed. The article offers an original interpretation of promising directions for the development of cryptocurrency payments in automotive services, including the integration of hybrid consensus solutions, institutional standardization, and adaptation to regional consumer behavior models. The material will be of interest to researchers in digital economy, transport innovations, financial technologies, and institutional governance, as well as practitioners working on the implementation of cryptocurrency payments in the automotive industry.